Aloïs Humbert (1829–1887), the first professional curator of natural history in Geneva. Issue 2 (October 2020) - Hollier, John; Hollier, Anita
Abstract : Aloïs Humbert was the first scientist employed by the Musée académique de Genève, but his career as a whole has a much closer resemblance to his "gentleman scientist" contemporaries such as Henri de Saussure and Alphonse Pictet (both of whom also studied under François-Jules Pictet and contributed to the development of the museum) than to that of his successor in the post, Godefroy Lunel. His career is presented to throw light on the professionalization of science in nineteenth-century Geneva, and it is suggested that his prestige raised the status of the role of museum scientist, to the benefit of his successors.